The Aristotelian Strain in Modern Environmental Virtue Ethics: Some Challenges and Some Underexplored Opportunities - Catana, Leo (Environmental ethics, 2024)
This article offers a conceptual clarification of the Aristotelian component in environmental virtue ethics (EVE). It demonstrates that throughout the last four decades, contributors to EVE have favored an Aristotelian foundation (though a Humean base also has been proposed), and it presents six theoretical challenges and two underexplored possibilities premised on such an Aristotelian foundation of EVE. These two possibilities concern: 1) Aristotle's notion of the city-state (polis), denoting not only a densely populated area, but also agricultural land outside the city-walls, implying agrarian virtues were implicit in the Aristotelian framework; this is valuable to modern agriculture, and the ways in which environmentally friendly virtues are integrated into food production and consumption. 2) Aristotle's understanding of well-being (eudaimonia) as existing not only at an individual level, but also at a collective level; the latter is relevant to the prospect of upscaling eudaimonia to a structural level, within the limits of an ecologically sustainable citizenship.